Rethinking How Humanities Think: Daring and "do / make / think". - Parker, Lindsay; Gifford, James (English Studies in Canada, 2012)
The article offers authors' insight on the institutional thinking and solidarity within the humanities. The authors argue on the adoption of institutional thinking that will create solidarity and understanding on academic community, particularly on the universities. They mention that the thinking of individuals together with institutional thinking can identify the contrast and irrational appearance of thinking, doing and making in the modern university.